Assessment of Hydrocarbon Pollution in Groundwater Using Electrical Resistivity Method - Adeoti, Lukumon; Anukwu*, Geraldine; Ademoye, Saheed; Adegbite, Joseph; Adigun, Emmanuel; Adeogun, Oluwakemi (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Hydrocarbon contamination of the groundwater system is a problem facing residents of Ejigbo, Lagos, Southwestern Nigeria. The area hosts the busiest satellite petroleum depots in Nigeria, and residents have attributed pollution of the groundwater system to hydrocarbon spills from possible pipeline leakages. This study aimed to identify and characterize the source and extent of the groundwater system contamination in the study area. The electrical resistivity method was adopted, comprising 2D Electrical resistivity imaging (ERI) and Vertical Electric Sounding (VES) techniques. Data acquired were processed and analyzed to obtain geoelectric sections, longitudinal conductance map and 2D ERI sections for the study area. Three distinct geoelectric zones were delineated, with the intermediate zone identified as the contaminated shallow aquiferous unit. This unit's resistivity values ranged from about 400 - 5000 ohm-m at a depth of 5 - 35 m. On the 2D ERI sections, possible locations of pipeline leakages were identified. On some ERI sections, a linear feature with resistivity value less than 300 ohm-m was observed from the surface down the depth of the entire section, truncating the horizontal flow of the contaminated unit. Generally, the results indicate that the contamination of the shallow aquifer in the area is widespread and mitigation measures should be urgently undertaken. Keywords: leakages; contamination; geoelectric sections; longitudinal conductance; aquifer; pipeline; groundwater system *Corresponding author: Tel.: (+234) 905 638 6645 E-mail: ganukwu@unilag.edu.ng